Czech Republic : 2021 Article IV Consultation-Press Release; Staff Report; Supplementary Information; and Statement by the Executive Director for the Czech Republic. (IMF Staff Country Reports; Country Report ;, 2022)
The Czech Republic entered the pandemic on a strong economic footing. Amid another surge in virus infections, the outlook is for a continued rebound in activity. However, the risks are tilted to the downside. Inflation remained marginally above the upper tolerance band in 2020 and increased substantially in late 2021. Pressures in the labor market remain. Macrofinancial vulnerabilities persist as house price growth has reached record highs amid significant risk-taking by lenders.